(untitled) (Journal of the College of Basic Education, 2022)
Attention has increased globally, regionally, and locally in environmental issues due to their direct impact on humans through the exacerbation of the problem of environmental pollution, as its effects are considered one of the most prominent problems that have emerged recently that left social, health and economic effects and were caused by human behavior, and that Iraq is located in the western end of the continent of Asia near the Arabian Gulf And its geographical location will be a candidate home for the spread of diseases, which will have a significant impact on public health due to dust storms, high temperatures and lack of vegetation. Today, the phenomenon of Iraqi environmental pollution has become one of the major problems facing the health of society, whether through polluted water and high degrees.